Predictions for the Isolated Prompt Photon Production at the LHC at s = 13 TeV - Muhammad Goharipour; Hossein Mehraban (Advances in High Energy Physics)
The prompt photon production in hadronic collisions has a long history of providing information on the substructure of hadrons and testing the perturbative techniques of QCD. Some valuable information about the parton densities in the nucleon and nuclei, especially of the gluon, can also be achieved by analysing the measurements of the prompt photon production cross section whether inclusively or in association with heavy quarks or jets. In this work, we present predictions for the inclusive isolated prompt photon production in pp collisions at center-of-mass energy of 13 TeV using various modern PDF sets. The calculations are presented as a function of both photon transverse energy ETγ and pseudorapidity ηγ for the ATLAS kinematic coverage. We also study in detail the theoretical uncertainty in the cross sections due to the variation of the renormalization, factorization, and fragmentation scales. Moreover, we introduce and calculate the ratios of photon momenta for different rapidity regions and study the impact of various input PDFs on such quantity.